Trends in diabetes mortality identified from death certificates in Colombia, 1979-2017 - Pablo Chaparro-Narváez; Nelson J. Alvis-Zakzuk; Diana Díaz-Jiménez; Carlos Castañeda-Orjuela (Pan American Health Organization, 2021)
Objective. To describe the mortality trends of diabetes mellitus (DM) in Colombia, by sex and age group, from 1979 to 2017. Methods. We carried out an ecological study using mortality data from the Colombian National Administrative Department of Statistics. Crude and age-standardized annual mortality rates per 100 000 people were estimated. Trends of standardized rates were described by sex and age groups. Joinpoint regression models were performed to study mortality trends. Results. Throughout the whole period, the total number of DM recorded deaths in Colombia was 200 650, 58% (116 316) in women (p<0.05). The age-standardized mortality rates (ASMR) by sex increased from 13.2 to 26.6 deaths per 100 000 in women and from 10.1 to 22.7 in men from 1979 to 1999. We observed a decrease from 26.6 to 15.4 per 100 000 in women, and from 22.7 to 15.9 in men for the period 1999-2017. The joinpoint regression analysis showed that the average annual percentage change of the period did not vary in both sexes (men: -0.2%, 95% CI -1.0 to 1.4%; women: 0.7%, 95% CI -0.1 to 1.6%). Conclusions. The DM mortality showed a decreasing trend after 2000 in women and 2004 in men. Primary and secondary prevention programs must continue to be strengthened for an earlier diagnosis of diabetes.